Role of glycine in nociceptive and non‐nociceptive bladder reflexes and pudendal afferent inhibition of these reflexes in cats. Issue 7 (5th July 2015) - Rogers, Marc J.; Shen, Bing; Reese, Jeremy N.; Xiao, Zhiying; Wang, Jicheng; Lee, Andy; Roppolo, James R.; de Groat, William C.; Tai, Changfeng
Abstract : Aim: This study examined the role of glycinergic transmission in nociceptive and non‐nociceptive bladder reflexes and in inhibition of these reflexes by pudendal nerve stimulation (PNS). Methods: Cystometrograms (CMGs) were performed in α‐chloralose anesthetized cats by intravesical infusion of saline or 0.25% acetic acid (AA) to trigger, respectively, non‐nociceptive or nociceptive bladder reflexes. PNS at 2 or 4 times threshold (T) intensity for inducing anal twitch was used to inhibit the bladder reflexes. Strychnine (a glycine receptor antagonist) was administered in cumulative doses (0.001–0.3 mg/kg, i.v.) at 60–120 min intervals. Results: Strychnine at 0.001–0.3 mg/kg significantly ( P  < 0.05) increased bladder capacity and reduced contraction amplitude during saline CMGs but did not change these parameters during AA CMGs except at the 0.3 mg/kg dose which increased bladder capacity. Strychnine did not alter PNS inhibition during saline CMGs except at the highest dose at 2T intensity, but significantly ( P  < 0.05) suppressed PNS inhibition during AA CMGs after 0.001–0.003 mg/kg doses at 2T and 4T intensities. During AA CMGs strychnine (0.3 mg/kg) also unmasked a post‐PNS excitatory effect that significantly reduced bladder capacity after termination of PNS. Conclusions: Glycinergic inhibitory neurotransmission in the central nervous system plays an unexpected role to tonically enhance the magnitude and reduce the bladder volume threshold for triggering the non‐nociceptive bladder reflex. This is attributable to inhibition by glycine of another inhibitory mechanism. Glycine also has a minor role in PNS inhibition of the nociceptive bladder reflex. Neurourol. Urodynam. 35:798–804, 2016 . © 2015 Wiley Periodicals, Inc.